Design and Synthesis of 3-(3-Chloro-4-substituted phenyl)-4-(pyridin-4-yl)-1H-pyrazole-1-carboxamide Derivatives and Their Antiproliferative Activity Against Melanoma Cell Line - El-Gamal, Mohammed I.; Oh, Chang-Hyun (WILEY-V C H VERLAG GMBH, 2011)
Design and synthesis of new 3,4-diarylpyrazole-1-carboxamide derivatives are described. Their antiproliferative activity against A375 human melanoma cell line was tested and the effect of substituents on the diarylpyrazole scaffold was investigated. The pharmacological results indicated that most of the synthesized compounds showed moderate activity against A375, compared with Sorafenib. On the other hand, compounds Ia, Ie, IIb, and IIh were more potent than Sorafenib. In addition, compound IIa was equipotent to Sorafenib. Among all of these derivatives, compound IIb which has diethylamino and phenolic moieties showed the most potent antiproliferative activity against A375 human melanoma cell line. Virtual screening was carried out through docking of the most potent compound IIb into the domain of V600E-b-Raf and the binding mode was studied.
Keywords: REFRACTORY SOLID TUMORS; FACTOR RECEPTOR INHIBITOR; RAF KINASE; METASTATIC MELANOMA; PHASE-I; BAY-43-9006; SORAFENIB; THERAPY; PHARMACOKINETICS; INTERLEUKIN-2